Academic library collaboration to optimize library services - Gunadi, Zarra Zakiyyah Izzaturrahmah; Prijana; Sias, James Nicolo (Record and Library Journal, 2023)
Background of the study: College libraries as centers for quality knowledge management should strive to optimize their services so as to meet the needs of users.  However, it is not possible for libraries to meet all the needs of their users due to certain limitations, so collaboration is necessary. Purpose: This study explains the implementation of Widyatama and Brawijaya University Library collaboration to optimize their services, including organizational structure and collaboration tools, as well as its impacts. Method: This research uses qualitative descriptive methods with data collection techniques through observation, interviews, and literature studies. Findings: The collaboration uses the MoA and has formed a special unit. In its implementation, there are still some lackings. In addition, this collaboration has had more impact especially related to service quality, such as ease of information access and sharing. Conclusion: College library collaboration can improve the quality of education and research and make the institutions that house them more prime through increasing access and quality of services, efficient management of information resources, and empowering academic libraries. This research makes a new contribution in the understanding and implementation of collaboration between college libraries as an effort to optimize library services.